2016
DOI: 10.1002/anie.201609357
|View full text |Cite
|
Sign up to set email alerts
|

Living Cationic Polymerization of Vinyl Ethers through a Photoinduced Radical Oxidation/Addition/Deactivation Sequence

Abstract: A new photoinitiating system for living cationic polymerization of vinyl ethers is reported. In the current approach, visible-light irradiation of dimanganese decacarbonyl (Mn (CO) ) in the presence of an alkyl bromide results in the formation of carbon-centered radicals. The photochemically generated radicals were then oxidized by diphenyliodonium ions to the corresponding cations. These cations can add vinyl ether monomers, which are then rapidly deactivated by the bromide anions to give α-halide functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 56 publications
0
76
0
5
Order By: Relevance
“…[4][5][6][7][8][9][10][11] As the name suggests, these photoredox catalysts harnesses the energy of visible light to accelerate a chemical reaction through electron transfer processes. [5,[14][15][16][17][18][19][20][21][22][23] Inspired by this, Boyer and co-workers have recently utilized photoredox catalysts, [4,8,17,18] such as pheophorbide a (PheoA) and zinc tetraphenylporphine (ZnTPP), to mediate photoinduced electron/energy transfer reversible addition-fragmentation chain transfer (PET-RAFT) polymerization (Scheme 1). [12] The property of compatibility has led to some recent developments in the field of visible-light photocatalysis, where different catalysts are utilized to perform complex organic reactions in a single pot.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] As the name suggests, these photoredox catalysts harnesses the energy of visible light to accelerate a chemical reaction through electron transfer processes. [5,[14][15][16][17][18][19][20][21][22][23] Inspired by this, Boyer and co-workers have recently utilized photoredox catalysts, [4,8,17,18] such as pheophorbide a (PheoA) and zinc tetraphenylporphine (ZnTPP), to mediate photoinduced electron/energy transfer reversible addition-fragmentation chain transfer (PET-RAFT) polymerization (Scheme 1). [12] The property of compatibility has led to some recent developments in the field of visible-light photocatalysis, where different catalysts are utilized to perform complex organic reactions in a single pot.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Yagci and coworkers [74] reported a novel photoinitiating system for living cationic polymerization of vinyl ethers eliminating the requirement for the metal halides by using Mn 2 (CO) 10 photochemistry. As presented in Scheme 10, in the described approach, visible-light irradiation of Mn 2 (CO) 10 in the presence of an alkyl bromide results in the formation of carbon-centered radicals.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Recently,t he integration of photo-mediated synthesis with reversible-deactivation radical polymerization (RDRP), including nitroxide-mediated polymerization (NMP), atom-transfer radical polymerization (ATRP), and reversible addition-fragmentation chain-transfer (RAFT) polymerization, is as ignificant advancement in this field. [3] So far, in this field, great progress has been made in the groups led by Hawker and Fors, [4] Matyjaszewski, [5] Yagci, [6] Miyake, [7] Boyer, [8][9][10] Qiao, [11] Haddleton and Anastasaki, [12] Johnson, [13,14] Boydston, [15] Egap, [16] and many others. [3] So far, in this field, great progress has been made in the groups led by Hawker and Fors, [4] Matyjaszewski, [5] Yagci, [6] Miyake, [7] Boyer, [8][9][10] Qiao, [11] Haddleton and Anastasaki, [12] Johnson, [13,14] Boydston, [15] Egap, [16] and many others.…”
Section: Heteroatom-doped Carbon Dots (Cds) As Ac Lass Of Metal-free mentioning
confidence: 99%
“…

Ak ey challenge of photoregulated living radical polymerization is developing efficient and robust photocatalysts.Now carbon dots (CDs) have been exploited for the first time as metal-free photocatalysts for visible-light-regulated reversible addition-fragmentation chain-transfer (RAFT) polymerization. [3] So far, in this field, great progress has been made in the groups led by Hawker and Fors, [4] Matyjaszewski, [5] Yagci, [6] Miyake, [7] Boyer, [8][9][10] Qiao, [11] Haddleton and Anastasaki, [12] Johnson, [13,14] Boydston, [15] Egap, [16] and many others. PET-RAFT polymerization of various monomers with temporal control, narrowdispersity ( % 1.04), and chain-endfidelity was achieved.Besides,itwas demonstrated that the CD-catalyzed PET-RAFT polymerization was effectively performed under natural solar irradiation.

Inspired by the solar-driven biosynthesis of proteins with high chain end fidelity and sequence control, macromolecular research has been focused on the exploitation of light to regulate modern polymer synthesis for ab etter control over the polymerization process.

…”
mentioning
confidence: 99%